2011
DOI: 10.1093/humrep/der132
|View full text |Cite
|
Sign up to set email alerts
|

The role of sperm oxidative stress in male infertility and the significance of oral antioxidant therapy

Abstract: Oxidative stress in the male germ line is thought to affect male fertility and impact upon normal embryonic development. Accordingly, fertility specialists are actively exploring the diagnosis of such stress in spermatozoa and evaluating the possible use of antioxidants to ameliorate this condition. In this review, evidence for the presence of oxidative stress in human spermatozoa, the origins of this phenomenon, its clinical significance in the aetiology of male infertility and recent advances in methods for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
291
1
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(313 citation statements)
references
References 136 publications
9
291
1
12
Order By: Relevance
“…There are varied reports [116][117][118] on the efficiency of various antioxidant therapy in infertile men. Recent meta analysis [119,120] of these studies suggest that antioxidant therapy is beneficial and improves various indices of male fertility. However antioxidants should only be administered in cases with increased free radical levels as majority of enzymatic reactions in our body functions under redox conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are varied reports [116][117][118] on the efficiency of various antioxidant therapy in infertile men. Recent meta analysis [119,120] of these studies suggest that antioxidant therapy is beneficial and improves various indices of male fertility. However antioxidants should only be administered in cases with increased free radical levels as majority of enzymatic reactions in our body functions under redox conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of dietary intake antioxidant on semen parameters were documented in several studies (38,39). Some authors reported that OLE possessed antioxidant property and increased diminished antioxidant enzyme activities in different tissue (40,41).…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative stress is a wellknown mechanism of chemical-and/or carcinogen-induced tumours, resulting from an imbalance between the production of reactive oxygen species (ROS) and their efficient removal by available antioxidant defence systems (Valko et al, 2006). Notably, oxidative stress together with associated sperm DNA damage and apoptosis have been clearly implicated in the pathogenesis of idiopathic infertility in men (Agarwal and Said, 2005;Aitken et al, 2003;Gharagozloo and Aitken, 2011;Sanocka et al, 1997). Since oxidative stress is thought to be involved in the pathogenesis of idiopathic male infertility, polymorphisms of NAT2 may represent potential candidates for disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%